Frequency characteristics of meta-language words in Russian and Chinese languages (according to frequency dictionaries data) - Gao , Wanrou (Journal of the Belarusian State University. Philology, 2024)
The article analyses the frequency characteristics of meta-language lexemes selected by the method of continuous sampling from the first thousand words in Russian and Chinese frequency dictionaries. The aim of the study is to compare the relevance of linguistic and communicative phenomena in situations of meta-language reflection in Russian and Chinese languages. Common perceptions regarding the importance of communicative actions, oral or written texts, and language units were identified, as recorded in the frequency characteristics of meta-language lexemes. Similarities and differences in the semantic and quantitative patterns of the meta-language lexemes were established. It has been shown that the frequency of meta-language lexeme reflects its active use in communication and can convey naive linguistic knowledge in Russian and Chinese linguocultures.